Jangha (wall) of the Suswani Mata Temple on the west and north - Temples of India Project Team (Jio Institute, 2024)
Seen here is the jangha (wall) of the Suswani Mata Temple on the west and north-facing sides. Each of these walls has five divisions in which the Bhadra (central offset) is the most protruding projection and subsidiary projections are offset to each other. This makes it a pancharatha (five ratha or projections on each side) variety of temple plans.